Pengaruh Persepsi Harga, Kualitas Produk, Dan Proses Transaksi Terhadap Kepercayaan Pelanggan Serta Dampaknya Pada Minat Beli Ulang Melalui Social Media Dan E-Commerce - Hizrian Lesty Prabowo; Triyono Arief Wahyudi (Research and Community Service UNIVERSITAS KALBIS, 2024)
This research aims to identify influence of price perception, quality, and transaction process on customer trust and its impact on repurchase intention trough social media and e-commerce. This research is done by quantitative research method with survey method on consumer who have done online shopping in social media and e-commerce in Jakarta. The sample was taken by purposive sampling method where 100 samples obtained were chosen based on predetermined criteria. The result of this research is (1) there is a significant influence between price perceptions on the establishment of trust in online purchases through social media and e-commerce, (2) there is no significant influence between the perception of quality towards the formation of trust in online purchasing through social media and e-commerce, (3) there is a significant influence between the process transaction on the establishment of trust in online purchasing through social media and e-commerce, (4) there is a significant influence between the belief on the decision of buy-back intention on the online purchase through social media and e-commerce.